Temporalités du street art et image des territoires en mutation - Clotilde Kullmann (EchoGéo)
The purpose of this article is to analyse the processes and some effects of the production and the valorisation of street art within urban regeneration, in the basis on a development operation in the Parisian metropolis (Zone d'Amenagement Concertée Paris Rive Gauche). A first part highlights the signals of the recognition of street art as a tool to create a positive territorial image, by urban and artistic actors. It shows then how the artistic practice is inspired by the characteristics and the experience of the urban regeneration. A second part focuses on some effects of the success of street art. On the one hand, it examines its temporal evolutions, turning from ephemeral to perennial forms, and questions the impacts of these evolutions. On the other hand, it studies the increase of graffitis, which could enrich the urban image by street art according to the criteria of acceptability of the public authorities.